Emperor : the gods of war - Iggulden, Conn.; Harper Collins (London : HarperCollins, 2006)
In 53 B.C., as the armies of Rome face each other in civil war, Julius Caesar struggles to fulfill his destiny as his military genius and appetite for glory are tested by Pompey and his troops and his longing for an ancient world of mysteries and a bewitching woman lead him to an uncertain future.
Adult
Keywords: Caesar, Julius -- Fiction; Emperors -- Fiction; Biographical fiction; Historical fiction; Rome -- History -- Civil War, 49-45 B.C. -- Fiction; Rome -- History -- Fiction